2018
DOI: 10.37358/rc.18.4.6202
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Activity of Some Acylhydrazones with Dibenzo[a,d][7]annulene Moiety

Abstract: Searching new antioxidants compounds to prevent or reduce the impact of oxidative stress on cells, we designed and synthesized several N-acylhydrazone derivatives with dibenzo[a,d][7]annulene moiety. In this work, a series of previously synthesized N-acylhydrazone derivatives bearing 5H-dibenzo[a,d][7]annulene moiety 7a-g were evaluated for antioxidant activity effect, using the DPPH method. The highest antioxidant activity was exhibited by the compound 7f containing in his molecule 4-hydroxy-3-methoxyphenyl f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Vaccine schedule includes a single dose, followed by a second dose 1-2 months later and afterwards a final dose 6 months later (63)(64)(65)(66)(67)(68). Current recommendation regarding male vaccination from CDC Advisory Committee on Immunization Practices are as follows: routine male vaccination beginning at the age of 11 or 12 years with either the quadrivalent or 9-valent vaccine, also vaccination for males aged between 13 and 21, who have not completed a three-dose cycle.…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 99%
“…Vaccine schedule includes a single dose, followed by a second dose 1-2 months later and afterwards a final dose 6 months later (63)(64)(65)(66)(67)(68). Current recommendation regarding male vaccination from CDC Advisory Committee on Immunization Practices are as follows: routine male vaccination beginning at the age of 11 or 12 years with either the quadrivalent or 9-valent vaccine, also vaccination for males aged between 13 and 21, who have not completed a three-dose cycle.…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 99%
“…Observational studies suggest an association between vitamin D deficiency and pregnancy complications [19][20][21][22]. A metanalysis of 31 studies, by Aghajafari et al concluded there is an increased risk for gestational diabetes, preeclampsia and intrauterine growth restriction in vitamin D deficient women [23].…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38]. A diet based on purine intake represent a risk factor for uric acid production which can lead to calcium oxalate stone formation [39,40].…”
Section: Resultsmentioning
confidence: 99%